2015
DOI: 10.1039/c5an00671f
|View full text |Cite
|
Sign up to set email alerts
|

Characterising cytotoxic agent action as a function of the cell cycle using fourier transform infrared microspectroscopy

Abstract: Fourier Transform Infrared (FTIR) micro-spectroscopy measurements were acquired to study infrared signatures of chemotherapeutic response as a function of the cell cycle. Renal carcinoma Caki-2 cells were exposed to IC50 doses of 5-fluorouracil and Paclitaxel for a period of 24 hours. The inherent cell cycle infrared signatures from untreated and drug-treated cells were successfully retrieved by the construction of a robust SVM able to discriminate the cell cycle phases of this cell line with an average accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
(129 reference statements)
1
15
0
Order By: Relevance
“…Here, the major DNA peaks have been explored to assess if one of the targets of BaP could in fact be DNA and to confirm that what was being monitored in this study was not simply cell death. One of the vibrations as a marker for the latter hypothesis is the carbonyl vibration for protein linking in the amide I band at 1657 cm −1 which has been reported to significantly decrease with apoptosis 48 . A visual inspection of the spectra in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the major DNA peaks have been explored to assess if one of the targets of BaP could in fact be DNA and to confirm that what was being monitored in this study was not simply cell death. One of the vibrations as a marker for the latter hypothesis is the carbonyl vibration for protein linking in the amide I band at 1657 cm −1 which has been reported to significantly decrease with apoptosis 48 . A visual inspection of the spectra in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This constitutes an unmatched approach for routine chemical proling of cells, allowing accurate examination of cellular environments and monitoring of drug bioavailability, biodistribution and target site accumulation aer administration, as well as drug delivery across biological barriers and cellular response to treatment. [30][31][32] Since cells are known to have specic vibrational spectroscopic signatures for different physiological conditions (regarding viability, cell cycle, apoptosis or stress), a correlation between a particular vibrational prole and a denite effect or mode of action should predictably be attained.…”
mentioning
confidence: 99%
“…47 They were able to follow progression during chemotherapy largely based on lipid IR absorptions, which have been demonstrated as a spectral marker of apoptosis. 48,49 They were unable to predict the treatment outcomes based on the PBMC spectra obtained in pre-treatment days, however, it was shown that FTIR spectroscopy could provide additional information on chemotherapeutic response of an individual patient basis; an application that may be vital to identify unexpected complications in real time as soon as they may appear during treatment.…”
Section: Analystmentioning
confidence: 99%